Implantación de un sistema contable para créditos comisa en la ciudad de Santo Domingo, período julio – septiembre 2013 - Vaca Bravo, Nelson Alberto (2014)
This research titled Implementation of an accounting system for Loan Comisa in the city of Santo Domingo, period July-September 2013, it is able to perform based on Rule 151 of the Academic System of the National University of Loja, because that is prior to obtaining engineering degree in Accounting and Auditing CPA requirement. The implementation of an accounting system credits Comisa developed according to the fulfillment of the objectives previously established to improve the accuracy and control of accounting and financial reporting of the organization making the owner be made aware of the relevance of scientific tools to manage support are in control of resources and decision -making. Thus, it was necessary to collect and organize the accounting information based on source documents, develop a plan and manual accounts to suit the needs of the company, raising the initial inventory, develop main and auxiliary books, so that they are the basis for structuring the financial statements that clearly exposed the real and reliable information. By implementing the proposal could be demonstrated that the accounting process can determine the income and expenditures for a given period with accuracy , providing valuable and reliable information in a timely manner to efficiently meet the tax and labor obligations moment, yes that should continue to use these daily records of transactions for financial statements attached to the laws to tax and accounting level , labor force who are to optimize resources and empower the assets of the organization are taken .